Pengaruh Information Involvement terhadap Impulsive Travel Behavior dengan Fear of Missing Out sebagai Mediator dan Destination Trust sebagai Moderator - Wan Suryani; Finta Aramita (Universitas Negeri Surabaya, 2026)
Digital tourism marketing increasingly relies on live streaming platforms to convey in-depth destination information. However, comprehensive studies on how information involvement is transformed into impulsive travel behaviour through psychological mechanisms remain limited. This study analyses the influence of information involvement on impulsive travel behaviour with Fear of missing out (FoMO) as a mediator and destination trust as a moderator. This study uses a quantitative, explanatory design. The researchers collected data from 300 respondents who actively use digital platforms as a source of travel information. The researchers analysed the data using Partial Least Squares-based Structural Equation Modelling (SEM-PLS). The results of the analysis show that information involvement significantly increases FoMO, and FoMO strongly encourages impulsive travel behaviour. Information involvement also directly affects impulsive travel behaviour. Mediation analysis confirms that FoMO partially mediates the relationship between information involvement and impulsive travel behaviour. Destination trust directly affects FoMO but does not moderate the relationship between information involvement and FoMO. These findings indicate that FoMO is more strongly shaped by emotional and social processes than by cognitive trust evaluations. This study enriches the tourism marketing literature by reconceptualising impulsive travel behaviour as a travel decision process, positioning FoMO as the primary emotional mechanism, and refining the theoretical position of destination trust in digital tourism. Practically, these findings emphasise the importance of managing information involvement and emotional attachment in live-streaming-based tourism marketing strategies.